Incidence, clinical characteristics and prognosis of tumor lysis syndrome following B-cell maturation antigen-targeted chimeric antigen receptor-T cell therapy in relapsed/refractory multiple myeloma - Zhang, Qiqi; Zu, Cheng; Jing, Ruirui; Feng, Youqin; Zhang, Yanlei; Zhang, Mingming; Lv, Yuqi; Cui, Jiazhen; Zhou, Linhui; Meng, Ye; Wang, Linqin; Cen, Zenan; et al. (Frontiers in Immunology, 2023)
Background Aims B-cell maturation antigen (BCMA)-targeted chimeric antigen receptor-T cell (CAR-T) therapy is used for refractory or relapsed multiple myeloma (r/r MM). However, CAR-T-related tumor lysis syndrome (TLS) has been observed. We aimed to elucidate the incidence, clinical and laboratory characteristics, and prognosis of CAR-T cell-related TLS. Methods Patients (n=105) with r/r MM treated with BCMA-targeted CAR-T cell therapy were included. Patient characteristics, laboratory parameters, and clinical outcomes were assessed. Results Eighteen (17.1%) patients developed TLS after BCMA-targeted CAR-T cell therapy. The median time till TLS onset was 8 days. Patients with TLS had steep rise in uric acid (UA), creatinine, and lactate dehydrogenase (LDH) within 6 days following CAR-T cell infusion and presented earlier and persistent escalation of cytokines (C-reactive protein [CRP], interleukin-6 [IL-6], interferon-γ [IFN-γ], and ferritin levels). All 18 patients had cytokine release syndrome (CRS), of which 13 (72.2%) developed grade 3–4 CRS. Three of 18 patients (16.7%) developed immune effector cell-associated neurotoxicity syndrome (ICANS): two patients with grade 1 ICANS and one with grade 2 ICANS. TLS development had a negative effect on the objective response rate (77.8% in the TLS group vs. 95.4% in the non-TLS group, p<0.01). During the median follow-up of 15.1 months, the median PFS was poorer of patients with TLS (median: 3.4 months in the TLS group vs. 14.7 months in the non-TLS group, p<0.001, hazard ratio [HR]=3.5 [95% confidence interval [CI] 1.5–8.5]). Also, TLS development exhibited significant effects on OS (median: 5.0 months in the TLS group vs. 39.8 months in the non-TLS group, p<0.001, hazard ratio [HR]=3.7 [95% CI 1.3–10.3]). TLS was associated with a higher tumor burden, elevated baseline creatinine and UA levels, severe CRS, pronounced CAR-T cell expansion, and corticosteroid use.Baseline serum UA and interferon-γ levels on day 3 were predictive of TLS. Conclusion TLS is a frequently observed CAR-T therapy complication and negatively influences clinical response and prognosis. Close monitoring for TLS should be implemented during CAR-T cell therapy, especially for those at high TLS risk.